The evolution of rehabilitation: a brief review. (Revista horizonte, 2013)
The evolution of rehabilitation, from the standpoint of exercise and movement, began in prehistory, as a means of survival. In the present history review it's had been divided into the following periods: a) Chinese, b) Indian, c) Egyptian, d) Greek, e) Birth of Medical Gymnastics, f) Roman, g) Medieval h) Rehabilitation in Latin America.